Capturing Genetic Variability and Identification of Promising Drought-Tolerant Lines in Exotic Landrace Derived Population Under Reproductive Drought Stress in Rice - Venkateshwarlu, Challa; Kole, Paresh Chandra; Paul, Pronob J.; Singh, Arun Kumar; Singh, Vikas Kumar; Kumar, Arvind (Frontiers in Plant Science, 2022)
Drought is one of the most predominant abiotic stresses in this century, leading to a drastic reduction in the yield of rainfed rice ecosystems. Breeding of drought-resilient rice variety is very much in demand for sustainable rice production in drought-prone rainfed ecology. An experiment was designed under irrigated non-stress and drought-stress situations involving an exotic drought-tolerant landrace and a high-yielding aromatic rice cultivar. An F2:4 derived population (Kasturi × Chao Khaw) of 156 lines was developed at IRRI South Asia Hub, Hyderabad, to assess the genetic variability, drought tolerance behavior, and identify promising breeding lines for different rice ecologies and drought breeding programs. Restricted maximum likelihood (REML) analysis using the mixed model approach revealed a considerable genetic variation in the population for yield and yield contributing traits in non-stress and drought-stress conditions. We observed very high heritability for all the selected traits under stress 2015 WS (73.8% to 85.3 %) and 2016 WS (72.4% to 93.5 %) and non-stress 2015 WS (68.2 % To 92.9 %) and 2016 WS (61.4% to 92.6 %) environments, indicating possible selection for grain yield under drought stress and non-stress with the same precision level. None of the secondary traits except harvest index and biomass included in our study showed a positive association with grain yield, indicating indirect selection’s ineffectiveness in improving yield under drought. A total of 48 promising lines were found to have a better yield than donor Chao Khaw (up to 38% advantage) and popular drought-tolerant cultivars Shabhagidhan (up to 48% advantage) in stress conditions and recommended rainfed upland ecology, 34 lines under the well-watered condition suited for rainfed lowland ecology. Overall, the study found 21 common lines that showed their superiority in non-stress and under-stress situations, fitting best in rainfed lowland ecology with occasional drought occurrence. The large genetic variation found in this population can be exploited further to develop a few forward breeding high-yielding lines with better drought tolerance capacity and in drought breeding programs.